Photoinduced post-modification of graphitic carbon nitride-embedded hydrogels: synthesis of 'hydrophobic hydrogels' and pore substructuring - Esen, Cansu; Kumru, Baris (Beilstein Journal of Organic Chemistry, 2021)
Hydrogels are a special class of crosslinked hydrophilic polymers with a high water content through their porous structures. Post-modifications of hydrogels propose an attractive platform so that a variety of fresh functions, which are not arising from initial monomers, could be accessible on a parental network. Photoinduced post-modification of hydrogels by embedding semiconductor nanosheets would be of high interest and novelty. Here, a metal-free semiconductor graphitic carbon nitride (g-CN)-embedded hydrogel as an initial network was synthesized via redox-couple initiation under dark conditions. Post-photomodification of so-formed hydrogel, thanks to the photoactivity of the embedded g-CN nanosheets, was exemplified in two scenarios. The synthesis of ‘hydrophobic hydrogel’ is reported and its application in delayed cation delivery was investigated. Furthermore, pores of the initial hydrogel were modified by the formation of a secondary polymer network. Such a facile and straightforward synthetic protocol to manufacture functional soft materials will be of high interest in near future by the means of catalysis and agricultural delivery.
Keywords: hydrophobic hydrogel; photoactive hydrogels; photomodification; pore modification; soft materials

(untitled) - Caló, E.; Khutoryanskiy, V. V. (Eur. Polym. J., 2015)

(untitled) - Li, L.; Yan, B.; Yang, J.; Huang, W.; Chen, L.; Zeng, H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Yuk, H.; Lin, S.; Ma, C.; Takaffoli, M.; Fang, N. X.; Zhao, X. (Nat. Commun., 2017)

(untitled) - Murakami, T.; Schmidt, B. V. K. J.; Brown, H. R.; Hawker, C. J. (Macromolecules, 2015)

(untitled) - Li, T.; Kumru, B.; Al Nakeeb, N.; Willersinn, J.; Schmidt, B. V. K. J. (Polymers (Basel, Switz.), 2018)

(untitled) - Chen, Q.; Chen, H.; Zhu, L.; Zheng, J. (J. Mater. Chem. B, 2015)

(untitled) - Li, Z.; Su, Y.; Xie, B.; Liu, X.; Gao, X.; Wang, D. (J. Mater. Chem. B, 2015)

(untitled) - Haque, M. A.; Kurokawa, T.; Gong, J. P. (Polymer, 2012)

(untitled) - Gao, G.; Du, G.; Cheng, Y.; Fu, J. (J. Mater. Chem. B, 2014)

(untitled) - Wang, Q.; Hou, R.; Cheng, Y.; Fu, J. (Soft Matter, 2012)

(untitled) - Djonlagic, J.; Lancuski, A.; Nikolic, M. S.; Rogan, J.; Ostojic, S.; Petrovic, Z. (J. Appl. Polym. Sci., 2017)

(untitled) - Liu, L.; Li, L.; Qing, Y.; Yan, N.; Wu, Y.; Li, X.; Tian, C. (Polym. Chem., 2016)

(untitled) - Klein, M.; Poverenov, E. (J. Sci. Food Agric., 2020)

(untitled) - Sampathkumar, K.; Tan, K. X.; Loo, S. C. J. (iScience, 2020)

(untitled) - Nayak, P. K.; Mahesh, S.; Snaith, H. J.; Cahen, D. (Nat. Rev. Mater., 2019)

(untitled) - Kumru, B.; Antonietti, M. (Adv. Colloid Interface Sci., 2020)

(untitled) - Liao, G.; He, F.; Li, Q.; Zhong, L.; Zhao, R.; Che, H.; Gao, H.; Fang, B. (Prog. Mater. Sci., 2020)

(untitled) - Gaddam, S. K.; Pothu, R.; Boddula, R. (Polym. Compos., 2020)

(untitled) - Barrio, J.; Shalom, M. (ChemCatChem, 2018)

(untitled) - Liu, Q.; Wang, X.; Yang, Q.; Zhang, Z.; Fang, X. (Appl. Surf. Sci., 2018)

(untitled) - Luo, B.; Song, R.; Geng, J.; Jing, D.; Zhang, Y. (Appl. Catal., B, 2018)

(untitled) - Han, Q.; Wang, B.; Zhao, Y.; Hu, C.; Qu, L. (Angew. Chem., Int. Ed., 2015)

(untitled) - Yang, Y.; Zeng, G.; Huang, D.; Zhang, C.; He, D.; Zhou, C.; Wang, W.; Xiong, W.; Song, B.; Yi, H.; Ye, S.; Ren, X. (Small, 2020)

(untitled) - Xu, G.; Xu, Y.; Zhou, Z.; Bai, Y. (Diamond Relat. Mater., 2019)

(untitled) - Sun, J.; Xu, J.; Grafmueller, A.; Huang, X.; Liedel, C.; Algara-Siller, G.; Willinger, M.; Yang, C.; Fu, Y.; Wang, X.; Shalom, M. (Appl. Catal., B, 2017)

(untitled) - Cao, Q.; Amini, S.; Kumru, B.; Schmidt, B. V. K. J. (ACS Appl. Mater. Interfaces, 2021)

(untitled) - Qin, J.; Wang, S.; Ren, H.; Hou, Y.; Wang, X. (Appl. Catal., B, 2015)

(untitled) - Lin, J.; Pan, Z.; Wang, X. (ACS Sustainable Chem. Eng., 2014)

(untitled) - Gong, X.; Yu, S.; Guan, M.; Zhu, X.; Xue, C. (J. Mater. Chem. A, 2019)

(untitled) - Giusto, P.; Cruz, D.; Heil, T.; Arazoe, H.; Lova, P.; Aida, T.; Comoretto, D.; Patrini, M.; Antonietti, M. (Adv. Mater. (Weinheim, Ger.), 2020)

(untitled) - Giusto, P.; Kumru, B.; Zhang, J.; Rothe, R.; Antonietti, M. (Chem. Mater., 2020)

(untitled) - Kiskan, B.; Zhang, J.; Wang, X.; Antonietti, M.; Yagci, Y. (ACS Macro Lett., 2012)

(untitled) - Fu, Q.; Ruan, Q.; McKenzie, T. G.; Reyhani, A.; Tang, J.; Qiao, G. G. (Macromolecules, 2017)

(untitled) - Kumru, B.; Cruz, D.; Heil, T.; Antonietti, M. (Chem. Mater., 2020)

(untitled) - Kumru, B.; Mendoza Mesa, J.; Antonietti, M.; Al-Naji, M. (ACS Sustainable Chem. Eng., 2019)

(untitled) - Sun, J.; Schmidt, B. V. K. J.; Wang, X.; Shalom, M. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Liu, J.; An, T.; Chen, Z.; Wang, Z.; Zhou, H.; Fan, T.; Zhang, D.; Antonietti, M. (J. Mater. Chem. A, 2017)

(untitled) - Ye, B.; Yao, C.; Yan, M.; Zhang, H.; Xi, F.; Liu, J.; Li, B.; Dong, X. (Macromol. Mater. Eng., 2019)

(untitled) - Kumru, B.; Molinari, V.; Hilgart, M.; Rummel, F.; Schäffler, M.; Schmidt, B. V. K. J. (Polym. Chem., 2019)

(untitled) - Thurston, J. H.; Clifford, A. J.; Henderson, B. S.; Smith, T. R.; Quintana, D.; Cudworth, K. F.; Lujan, T. J.; Cornell, K. A. (ACS Appl. Bio Mater., 2020)

(untitled) - Hu, C.; Lin, Y.-R.; Yang, H.-C. (ChemSusChem, 2019)

(untitled) - Shalom, M.; Inal, S.; Fettkenhauer, C.; Neher, D.; Antonietti, M. (J. Am. Chem. Soc., 2013)

(untitled) - Zhou, X.; Zhang, P.; Zhao, F.; Yu, G. (ACS Mater. Lett., 2020)

(untitled) - Sikder, A.; Pearce, A. K.; Parkinson, S. J.; Napier, R.; O’Reilly, R. K. (ACS Appl. Polym. Mater., 2021)

(untitled) - Kumru, B.; Cruz, D.; Heil, T.; Schmidt, B. V. K. J.; Antonietti, M. (J. Am. Chem. Soc., 2018)

(untitled) - Barrio, J.; Shalom, M. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - de Oliveira Ferreira, M. E.; Vaz, B. G.; Borba, C. E.; Alonso, C. G.; Ostroski, I. C. (Microporous Mesoporous Mater., 2019)

(untitled) - Yu, Y.; Miyawaki, J. (Carbon, 2020)

(untitled) - Barrio, J.; Volokh, M.; Shalom, M. (J. Mater. Chem. A, 2020)

(untitled) - Yandrapalli, N.; Robinson, T.; Antonietti, M.; Kumru, B. (Small, 2020)